2009
DOI: 10.1097/md.0b013e3181afa1c8
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiosis at the Turn of the Century

Abstract: Nocardia species is an uncommon pathogen that affects both immunosuppressed and immunocompetent patients. The clinical and microbiologic spectrum of nocardiosis has changed recently due to the widespread use of cotrimoxazole prophylaxis, the emergence of new types of immunosuppressed patients, and the improved identification of isolates using molecular techniques. Nocardia asteroides was traditionally considered the predominant organism, and prophylaxis with cotrimoxazole was considered almost universally prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
371
4
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(405 citation statements)
references
References 68 publications
21
371
4
9
Order By: Relevance
“…In our study, Nocardia prevalence in soil was 16.4%. The frequency of pathogenic Nocardia species acquired from soil samples in different regions of the world has been reported to be 5%-50% [27][28][29][30] .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In our study, Nocardia prevalence in soil was 16.4%. The frequency of pathogenic Nocardia species acquired from soil samples in different regions of the world has been reported to be 5%-50% [27][28][29][30] .…”
Section: Discussionsupporting
confidence: 52%
“…Increase in the infections caused by these organisms, with different clinical forms of systemic and disseminated forms of nocardiosis in transplant recipients, tuberculosis, liver cirrhosis, cancer, diabetes, AIDS and patients under treatment with immunosuppressive drugs and broad spectrum antibiotics in the world, reveals more importance of isolation and identification of these agents [2,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Various studies have shown that identification and isolation of these agents in soil of different areas help to diagnose nocardiosis [1] .…”
Section: Introductionmentioning
confidence: 99%
“…of which many are finally identified as Actinomycetes other than Nocardia. The lung is the major organ primarily affected, accounting for 60-70 % of all human nocardiosis (Minero et al, 2009). Mortality due to nocardiosis ranges from 40 to 80 % depending on the immune status of the patient and intervention therapy (Knollmann et al, 2000;Martínez Tomás et al, 2007;Minero et al, 2009;Peleg et al, 2007;Zeidman et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia is an aerobic actinomycete that can cause infections, including pneumonia, usually in association with immunosuppression, including HIV infection [67,68]. The clinical course is often chronic, although dissemination can occur and be associated with a high mortality [68].…”
Section: Staphylococcus Aureusmentioning
confidence: 99%